Mutating alfalfa COUMARATE 3-HYDROXYLASE using multiplex CRISPR/Cas9 leads to reduced lignin deposition and improved forage quality - Wolabu, Tezera W.; Mahmood, Kashif; Chen, Fang; Torres-Jerez, Ivone; Udvardi, Michael; Tadege, Million; Cong, Lili; Wang, Zengyu; Wen, Jiangqi (Frontiers in Plant Science, 2024)
Alfalfa (Medicago sativa L.) forage quality is adversely affected by lignin deposition in cell walls at advanced maturity stages. Reducing lignin content through RNA interference or antisense approaches has been shown to improve alfalfa forage quality and digestibility. We employed a multiplex CRISPR/Cas9-mediated gene-editing system to reduce lignin content and alter lignin composition in alfalfa by targeting the COUMARATE 3-HYDROXYLASE (MsC3H) gene, which encodes a key enzyme in lignin biosynthesis. Four guide RNAs (gRNAs) targeting the first exon of MsC3H were designed and clustered into a tRNA-gRNA polycistronic system and introduced into tetraploid alfalfa via Agrobacterium-mediated transformation. Out of 130 transgenic lines, at least 73 lines were confirmed to contain gene-editing events in one or more alleles of MsC3H. Fifty-five lines were selected for lignin content/composition analysis. Amongst these lines, three independent tetra-allelic homozygous lines (Msc3h-013, Msc3h-121, and Msc3h-158) with different mutation events in MsC3H were characterized in detail. Homozygous mutation of MsC3H in these three lines significantly reduced the lignin content and altered lignin composition in stems. Moreover, these lines had significantly lower levels of acid detergent fiber and neutral detergent fiber as well as higher levels of total digestible nutrients, relative feed values, and in vitro true dry matter digestibility. Taken together, these results showed that CRISPR/Cas9mediated editing of MsC3H successfully reduced shoot lignin content, improved digestibility, and nutritional values without sacrificing plant growth and biomass yield. These lines could be used in alfalfa breeding programs to generate elite transgene-free alfalfa cultivars with reduced lignin and improved forage quality.